(untitled) (Nordic Journal of African Studies, 2010)
It has been suggested that the linguistic forms used by speakers to address or refer to each other also send different social and cultural meanings such as the type of relationships between speaker and addressee, or the attitude of speaker towards addressee. In this paper I identify the key linguistic components in Dagbanli address forms: kinship terms, names, and titles and discuss the social and cultural values attached to each. I outline the different ways in which these elements are combined not only for the purpose of identifying the addressee or referent, but also for communicating other social meanings and attitudes like politeness, power and solidarity.